Prognostic Role of Optical Coherence Tomography in Outcome of Idiopathic full thickness Macular Hole Surgery - Uzma Haseeb, Muhammad Haseeb, Aziz ur Rehman, Tauseef Mehmood (Journal of Rawalpindi Medical College, 2022)
Abstract Purpose: To assess the prognostic value of Optical Coherence Tomography indices preoperatively in outcome of idiopathic full thickness macular hole surgery. Material & Methods: A Quasi experimental study was carried out at Al Ibrahim eye hospital, Karachi from June 2019 to Feb 2020. Patients between 50 to 70 years of age, including both genders with full thickness idiopathic macular hole on Optical Coherence Tomography (OCT) were included while patients with secondary causes of macular hole like trauma, myopia, detachment of retina with macular hole, macular hole with other causes of poor vision like corneal scaring, Age related macular degeneration and diabetic retinopathy were excluded. OCT measurements are basal diameter, height of macular hole, right and left arm length and derived indices are macular hole index (MHI) and hole form factor (HFF). Results: A total 33 patients including 23 (69.6%) male and 10(30.3%) females of idiopathic full thickness macular hole were taken. Patients mean age was 55.25±6.9. Among 33 patients, MHI (>0.5) was found in 21(63.6%) patients while 12 (36.3%) patients had MHI (< 0.5). In 25 patients HFF calculation was possible. 17(68%) patients had HFF (>0.9) while 8 (32%) patients had HFF (< 0.9). Anatomical and visual outcomes were assessed at 1st and 3rd month follow-up. Of 21 patients for MHI >0.5, vision improved (i.e. ≥ 6/18) in 15 (71.4%). Similarly, out of 17 patients for HFF > 0.9, 13 (76.47%) patients had improved vision post-operatively. Conclusion: Optical coherence tomography indices can be helpful to predict surgical outcomes of idiopathic full thickness macular hole surgery.